Antimicrobial Photodynamic Therapy in Combination with Nystatin in the Treatment of Experimental Oral Candidiasis Induced by Candida albicans Resistant to Fluconazole - Karem Janeth Rimachi Hidalgo; Juliana Cabrini Carmello; Cláudia Carolina Jordão; Paula Aboud Barbugli; Carlos Alberto de Sousa Costa; Ewerton Garcia de Oliveira Mima; Ana Claudia Pavarina (MDPI AG, 2019)
Background: It has been demonstrated that azole-resistant strains of Candida albicans have a greater resistance to antimicrobial photodynamic therapy (aPDT) when compared to their more susceptible counterparts. For this reason, the present study evaluated the efficacy of aPDT, together with nystatin (NYS), in the treatment of oral candidiasis in vivo. Methods: Mice were infected with fluconazole-resistant C. albicans (ATCC 96901). To perform the combined therapy, aPDT, mediated by Photodithazine (PDZ) and LED light, was used together with NYS. The efficacy of the treatments was evaluated by microbiological, macroscopic, histopathological and Confocal Scanning Laser Microscopy analyses of the lesions. The expression of p21 and p53, proteins associated with cell death, from the tongues of mice, was also performed. Results: The combined therapy reduced the fungal viability by around 2.6 log10 and decreased the oral lesions and the inflammatory reaction. Additionally, it stimulated the production of p53 and p21. Conclusions: The combined therapy is a promising alternative treatment for oral candidiasis induced by C. albicans resistant to fluconazole.